2021
DOI: 10.1111/ecog.05836
|View full text |Cite
|
Sign up to set email alerts
|

Expert‐based assessment of rewilding indicates progress at site‐level, yet challenges for upscaling

Abstract: Rewilding is gaining importance across Europe, as agricultural abandonment trajectories provide opportunities for large‐scale ecosystem restoration. However, its effective implementation is hitherto limited, in part due to a lack of monitoring of rewilding interventions and their interactions. Here, we provide a first assessment of rewilding progress across seven European sites. Using an iterative and participatory Delphi technique to standardize and analyze expert‐based knowledge of these sites, we 1) map rew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…However, the most important lesson that can be drawn from our study is that only passive conservation measures (e.g., closure of accesses, no entry areas) are not enough to ensure restoration success, and a correct management should include educational activities to stimulate a pro-environmental behaviour and lead visitors to act in a way that benefits the natural environment, or at least does not result in adverse environmental impacts (Kim 2012). In a recent review, Segar et al (2021) reported that the effectiveness of restoration projects is often constrained by external pressures (e.g., the socio-economic environment), and that the success highly relies on effective communication and policy mechanisms. Although it may be difficult for beach managers to identify the most effective strategies to promote pro-environmental behaviour, educating individuals on the value of coastal dunes is mandatory to influence their behaviour (Dodds and Holmes 2018).…”
Section: Integritymentioning
confidence: 88%
“…However, the most important lesson that can be drawn from our study is that only passive conservation measures (e.g., closure of accesses, no entry areas) are not enough to ensure restoration success, and a correct management should include educational activities to stimulate a pro-environmental behaviour and lead visitors to act in a way that benefits the natural environment, or at least does not result in adverse environmental impacts (Kim 2012). In a recent review, Segar et al (2021) reported that the effectiveness of restoration projects is often constrained by external pressures (e.g., the socio-economic environment), and that the success highly relies on effective communication and policy mechanisms. Although it may be difficult for beach managers to identify the most effective strategies to promote pro-environmental behaviour, educating individuals on the value of coastal dunes is mandatory to influence their behaviour (Dodds and Holmes 2018).…”
Section: Integritymentioning
confidence: 88%
“…This supports the adoption of rewilding at scale in policy and decision‐making to fulfill the goals of the post‐2020 biodiversity framework and the spirit of the declaration of the UN Decade on Ecosystem Restoration (Svenning 2020). However, an enabling policy environment is needed to facilitate actions at wide scales, and policy mechanisms at the national and international scale such as the European Common Agricultural Policy need to be adjusted for these strategies to scale‐up beyond individual sites (Segar et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on seven European rewilding sites, Segar et al (2021) quantify changes over time across three central rewilding components that aim to encompass key ecological processes that are essential for self‐organizing and complex systems: stochastic disturbances, trophic complexity and dispersal. They then use expert elicitation to measure progress along these components and find overall progress for five of the seven sites, and decrease in the two remaining sites, attributable to an increase in human forcing.…”
Section: Assessing Restoration Effectiveness Including Careful Consid...mentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon of arable land abandonment often has mixed effects on economic, social and ecological systems [17]. Positive effects have been found, in terms of ecological effects such as vegetation and soil recovery, water retention, and increased biodiversity [18][19][20][21]. However, more studies have reported negative effects which, in addition to affecting food security, have led to increased fire frequency, higher agricultural costs, and loss of traditional agricultural landscapes and cultural values, among others [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%